“Avaliação do Potencial Biológico e Análise Fitoquímica de Extrato Etanólico e Frações, Obtido de Folhas de Clusia Fluminensis Plank & Triana” - Perini, Flavio Mauricio (2020)
The researchers look at the secondary metabolites of potential allelopathic plants as an alternative for biological control, as well as the search for alternative therapeutic substances leads to an increase in the exploration of biodiversity in order to r